2013
DOI: 10.1002/aic.14035
|View full text |Cite
|
Sign up to set email alerts
|

Pressure drop in a split‐and‐recombine caterpillar micromixer in case of newtonian and non‐newtonian fluids

Abstract: Microreactors are very promising tools for the design of future chemical processes. For example, emulsions of very narrow size distribution are obtained at much lower energy consumption than the one spent with usual processes. Micromixers play thereby an eminent role. The goal of this study is to better understand the hydrodynamic properties of a split-and-recombine Caterpillar micromixer (CPMM) specially with regard to handling viscoelastic fluids, a topic hardly addressed so far in the context of micromixers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Several micromixers involving 3D serpentine and/or SAR structures [42][43][44][45][46][47][48][49][59][60][61][62][63][64][65][66][67]80,81] (type 3 in Table 1) have been proposed. The 3D serpentine path induces a stirring flow at each bend and generates a secondary flow to enhance mixing [43,45].…”
Section: D Design With Serpentine And/or Sar Structures (Type 3)mentioning
confidence: 99%
“…Several micromixers involving 3D serpentine and/or SAR structures [42][43][44][45][46][47][48][49][59][60][61][62][63][64][65][66][67]80,81] (type 3 in Table 1) have been proposed. The 3D serpentine path induces a stirring flow at each bend and generates a secondary flow to enhance mixing [43,45].…”
Section: D Design With Serpentine And/or Sar Structures (Type 3)mentioning
confidence: 99%
“…(c) Schematic of the internal structure of a ramp-like caterpillar micromixer that drives split-and-recombine mixing. Reprinted with permission from ref . Copyright 2013 Wiley-VCH.…”
Section: Overview Of Continuous Flow Methodsmentioning
confidence: 99%
“…Parallel lamination of the fluids into very thin interdigitated streams results in shorter stream interdiffusion distances, thus requiring shorter reactor lengths for mixing (Figure b). , Alternatively, chaotic advection can be achieved through careful design of the reactor architecture by implementing obstacles in the channel path, altering the wall with ridges or grooves, or by altering the reactor channel geometry from a straight line into a zigzag or serpentine pattern, which perturbs the flow and generates a transversal component to the velocity . For example, a micromixer, called the caterpillar mixer, developed by the Institute of Microtechnology Mainz (IMM), used the principle of splitting and recombining in which the two fluids are split into multiple streams (∼300) in a channel containing ramp-like structures (Figure c) . This structure facilitates subsequent recombination of the two fluid streams in both the horizontal and vertical directions through folding, reorientating, and recombining, resulting in superior mixing compared to typical, straight laminar flow devices.…”
Section: Overview Of Continuous Flow Methodsmentioning
confidence: 99%
“…Additionally, non‐Newtonian fluids with different power‐law indices were studied, and they found that at a fixed Reynolds number, mixing index increases with an increase of power‐law index value. Carrier et al 28 conducted experiments to examine the pressure drop in a caterpillar micromixer (CPMM) for Newtonian and several non‐Newtonian fluids. The results depicted that for Newtonian fluids, the friction factor scaling was related as f/2 = 24/Re.…”
Section: Introductionmentioning
confidence: 99%